Primary Prostatic Stromal Sarcoma: A Case Report and Review of the Literature - Enes Erul; Ömer Gülpınar; Diğdem Kuru Öz; Havva Berber; Saba Kiremitci; Yüksel Ürün (Medicina)
Background and Objectives: Primary prostatic stromal sarcoma is an exceptionally rare urological malignancy, constituting less than 0.1% of all prostatic cancers. It poses a significant clinical challenge due to its aggressive behavior and poor prognosis. Materials and Methods: We report the case of a 34-year-old male who presented with nonspecific lower urinary tract symptoms, including dysuria and increased urinary frequency. The initial diagnostic workup, including digital rectal examination and Magnetic Resonance Imaging (MRI), revealed a lobulated lesion within the prostate. A transurethral resection (TUR) was performed for diagnostic purposes, and histopathological examination revealed a “malignant mesenchymal tumor”. The patient underwent a laparoscopic radical prostatectomy. The pathology report confirmed the diagnosis of prostatic stromal sarcoma. The postoperative follow-up, including systemic CT and MRI, showed no evidence of recurrence or metastasis thus far. Results: Multidisciplinary management is essential for optimizing treatment outcomes in all urologic malignancies; however, it becomes particularly challenging and crucial in rare cases such as primary prostatic stromal sarcoma. In our case, the patient benefited from a coordinated approach involving urology, pathology, and oncology, underscoring the importance of collaborative care for rare and aggressive tumors like this. This case highlights the importance of early detection, complete surgical excision, and consideration of adjuvant therapies, given the aggressive nature of the disease. The role of novel therapeutic strategies, including immunotherapy and targeted therapies, is also discussed in the context of metastatic sarcomas. Conclusions: This case underscores the critical need for a comprehensive, multidisciplinary approach to managing primary prostatic stromal sarcoma. Ongoing research on innovative therapies offers hope for improved outcomes in metastatic stages.